Hip Hop Party Dance: Cardiorespiratory Profile and Responses to a Predefined Sequence. Issue 1 (March 2023) - Prates, Claudia Machado; Tsiouti, Nefeli; Fagundes, Alex de Oliveira; Reichert, Thaís; Wyon, Matthew; Haas, Aline Nogueira
Hip hop is a popular dance genre practiced worldwide that has gained popularity since the 1970s. Despite this, studies related to the area and its physiological demands are still scarce. The purpose of this study was to report the cardiorespiratory profile of a group of male and female hip hop dancers to determine the zones of intensity of a predefined hip hop party dance sequence. Eight Brazilian professional hip hop dancers, four women and four men, mean age 22 ± 2.3 years, participated in the study. Using a portable gas analyser (Cosmed K5) their cardiorespiratory variables were measured at two different times: first, during a maximal treadmill test and later during a predefined hip hop party dance sequence. Descriptive statistics (mean and standard deviation) were used for calculating the dependent variables: oxygen consumption (VO2 ), heart rate (HR), and the intensity zones for the predefined hip hop sequence. Data normality was verified using the Shapiro-Wilk test. The Mann-Whitney U-test was performed to check any sex-related difference (p < 0.01). No statistical difference between male and female dancers was found in the cardiorespiratory profile and responses to the predefined hip hop party dance sequence. On the treadmill, the participants' VO2peak was 57.3 ± 12.7 ml·kg -1 ·min -1, and HRmax was 190.0 ± 9.1 b·min -1 . The predefined hip hop party dance sequence was mainly (61%) performed in the moderate aerobic zone. However, when the dancers jumped, the intensity of the sequence increased. This information could be used to develop a specific supplementary training protocols for hip hop dancers to improve their physiological fitness parameters and reduce the incidence of injury.